Diagnosis and treatment of invasive fungal infections: looking ahead. (23rd March 2019) - Sanguinetti, Maurizio; Posteraro, Brunella; Beigelman-Aubry, Catherine; Lamoth, Frederic; Dunet, Vincent; Slavin, Monica; Richardson, Malcolm D
Abstract: Improved standards of care depend on the development of new laboratory diagnostic and imaging procedures and the development of new antifungal compounds. Immunochromatography technologies have led to the development of lateral flow devices for the diagnosis of cryptococcal meningitis and invasive aspergillosis (IA). Similar devices are being developed for the detection of histoplasmosis that meet the requirements for speed (∼15 min assay time) and ease of use for point-of-care diagnostics. The evolution of molecular tools for the detection of fungal pathogens has been slow but the introduction of new nucleic acid amplification techniques appears to be helpful, for example T2Candida. An Aspergillus proximity ligation assay has been developed for a rapid near-patient bedside diagnosis of IA. CT remains the cornerstone for radiological diagnosis of invasive pulmonary fungal infections. MRI of the lungs may be performed to avoid radiation exposure. MRI with T2-weighted turbo-spin-echo sequences exhibits sensitivity and specificity approaching that of CT for the diagnosis of invasive pulmonary aspergillosis. The final part of this review looks at new approaches to drug discovery that have yielded new classes with novel mechanisms of action. There are currently two new classes of antifungal drugs in Phase 2 study for systemic invasive fungal disease and one in Phase 1. These new antifungal drugs show promise in meeting unmet needs with oral and intravenous formulations available and some with decreased potential for drug–drug interactions. Novel mechanisms of action mean these agents are not susceptible to the common resistance mechanisms seen in Candida or Aspergillus . Modification of existing antifungal susceptibility testing techniques may be required to incorporate these new compounds.